Anisotropies and magnetic phase transitions in insulating antiferromagnets determined by a Spin-Hall magnetoresistance probe - Lebrun, Romain; Ross, Andrew; Gomonay, Olena; Bender, S. A.; Baldrati, L.; Kronast, F.; Qaiumzadeh, Alireza; Sinova, Jairo; Brataas, Arne; Duine, R. A.; Klaeui, M. (Communications Physics, 2019)
Antiferromagnets possess a number of intriguing and promising properties for electronic devices, which include a vanishing net magnetic moment and thus insensitivity to large magnetic fields and characteristic terahertz frequency dynamics. However, probing the antiferromagnetic ordering is challenging without synchrotron-based facilities. Here, we determine the material parameters of the insulating iron oxide hematite, α-Fe2O3, using the surface sensitive spin-Hall magnetoresistance (SMR). Combined with a simple analytical model, we extract the antiferromagnetic anisotropies and the bulk Dzyaloshinskii-Moriya field over a wide range of temperatures and magnetic fields. Across the Morin phase transition, we show that the electrical response is dominated by the antiferromagnetic Néel vector rather than by the emergent weak magnetic moment. Our results highlight that the surface sensitivity of SMR enables access to the magnetic anisotropies of antiferromagnetic crystals, and also of thin films, where other methods to determine anisotropies such as bulk-sensitive magnetic susceptibility measurements do not provide sufficient sensitivity.
CRIS-Team Scopus Importer:2023-03-27